Application of suppressive subtractive hybridisation technique to isolate differentially expressed genes in Rhipicephalus appendiculatus ticks following infection by Theileria parva - Obura, M.; Skilton, Robert A.; Villiers, Etienne P. de; Kutima, H.; Bishop, Richard P. (Tanzania Society for Animal Production, 2006)
Tick salivary gland proteins are responsible for suppression/modulation of host immune responses and subsets of such genes whose expression is modified by Theileria parva infection would be candidates for inclusion in anti-tick/anti-pathogen combination vaccines. We used subtractive hybridisation to screen mRNAs in T. parva infected and uninfected Rhipicephalus appendiculatus salivary gland cDNA and identified 20 transcripts whose expression was modulated in respect to infection. Out of these, 15 were up regulated and 5 down regulated in response to infection by the pathogen. The identities of the isolated clones were determined by searches on RaGI (www.tigr.org/tigr-scripts/tgi), T. parva CDS and nucleic research database on proteins and nucleic acids using BLAST and other algorithms. Based on this analysis, the sequences were divided into three categories: those responsible for modifying host immune responses to the tick, transport molecules (including a putative Na+/K+ ATPase) and previously unidentified genes.